The rGel/BLyS Fusion Toxin Inhibits Diffuse Large B-cell Lymphoma Growth In Vitro and In Vivo - Mi-Ae Lyu; Deepak Rai; Kwang Seok Ahn; Bokyung Sung; Lawrence H. Cheung; John W. Marks; Bharat B. Aggarwal; Ricardo C.T. Aguiar; Varsha Gandhi; Michael G. Rosenblum (Neoplasia: An International Journal for Oncology Research, 2010)
Diffuse large B-cell lymphoma (DLBCL) is an aggressive subtype of B-cell non-Hodgkin lymphoma (NHL) and accounts for 30%to 40%of NHL. Molecules targeting nuclear factor-κB (NF-κB) are expected to be of therapeutic value in those tumors where NF-κB seems to play a unique survival role such as activated B-cell (ABC)-subtype DLBCL. We previously generated a rGel/BLyS fusion toxin for receptor-mediated delivery of the rGel toxin specifically to malignant B cells. In this study, we examined this fusion toxin for its ability to suppress DLBCL growth in vitro and in vivo. rGel/BLyS was specifically cytotoxic to DLBCL lines expressing all three BLyS receptors and constitutively active NF-κB. Treatment with rGel/BLyS induced down-regulation of the phosphorylation of inhibitory subunit of NF-κB (IκB-α), inhibition of NF-κB DNA-binding activity, and accumulation of IκB-α. In agreement with these results, we additionally found that rGel/BLyS downregulated levels of several NF-κB targets including Bcl-xL, Mcl-1, survivin, and x-chromosome linked inhibitor-of-apoptosis. Treatment also induced up-regulation of Bax and apoptosis through caspase-3 activation and poly ADP-ribose polymerase cleavage. Importantly, rGel/BLyS significantly inhibited tumor growth (P < .05) in a DLBCL xenograft model. Thus, our results indicate that rGel/BLyS is an excellent candidate for the treatment of aggressive NHLs that are both dependent on NF-κB and are resistant to conventional chemotherapeutic regimens.